Can a 2D planar model more accurately determine locations of contact developed by the femoral condyles on the tibial insert in total knee arthroplasty than the penetration method?. (March 2022) - Simileysky, Alexander; Hull, M.L.
Abstract: Knowledge of the anterior-posterior (AP) tibial contact locations is useful in assessing wear of tibial inserts and detecting posterior rim loading. The objectives of this study were to 1) create a new 2D planar model to determine AP tibial contact locations, 2) use the 2D planar model to determine AP tibial contact locations for cadaveric TKA knees, and 3) determine whether errors of the 2D planar model are lower than those of the penetration method. A slopes-of-sagittal profiles (SSP) model was created using mathematical functions to simulate articular surfaces of the tibial insert and femoral condyles. AP tibial contact locations were computed using the model and the penetration method and simultaneously measured with a custom tibial force sensor in 10 cadaveric TKA knees at 0°, 30°, 60°, and 90° of flexion in each compartment during passive motion. For each method, the overall bias, overall precision, and overall root mean square error (RMSE) were calculated from the differences between the computed AP tibial contact locations and the measured locations. The SSP model had an overall bias of 0.6 mm and precision of 2.8 mm which were significantly greater than the overall bias of −0.1 mm (p = 0.0369) and overall precision of 2.0 mm (p = 0.0021) of the penetration method. A planar model based on the analysis of single-plane radiographs did not decrease overall errors in AP tibial contact locations compared to the penetration method.